NoiBene, a Group Intervention for Promoting Mental Health Among University Students: A Study Protocol for a Randomized Controlled Trial - Di Consiglio, Micaela; Merola, Sheila; Satta, Chiara; Pascucci, Tiziana; Violani, Cristiano; Couyoumdjian, Alessandro (Frontiers in Psychology, 2022)
University students' mental health has become a public health issue since increasingly students report high levels of psychological distress. Mental health difficulties influence students' lives, such as academic performance, relationships satisfaction, and quality of life. Moreover, different kinds of obstacles often hinder help-seeking behavior. Such evidence strongly suggests the need to implement prevention and promotion strategies to increase health and well-being in educational contexts. This article presents a study protocol for implementing and evaluating NoiBene, an evidence-based group intervention that aims to promote mental health and well-being, improve a series of transversal competencies (e.g., emotional awareness, commitment to values, assertiveness, goal setting), and decrease dysfunctional transdiagnostic mechanisms (i.e., perfectionism, repetitive thinking, experiential avoidance). A randomized controlled trial will be conducted to evaluate the protocol's efficacy. Participants will be assigned to one of the three conditions: the NoiBene Group condition (NB-G), the NoiBene guided web-based condition (NB-WB) or the waiting-list condition (WLC). The NB-G intervention consists of six face-to-face group meetings, each dedicated to specific issues related to well-being or vulnerabilities. Every meeting includes an explanation of the theoretical contents, individual and group exercises, and role-plays. The NB-WB intervention covers the same topic addressed in the NB-G intervention. In this case, participants carry out a series of online modules, including theoretical explanations, practical exercises, useful activities, and self-monitoring tools. Students will individually meet the Tutor once every two weeks. The primary outcome will include an increase in mental health and well-being. Secondary outcomes will include changes in emotional awareness, assertiveness, perfectionism, rumination, worry, self-criticism, experiential avoidance, and academic performance and satisfaction. We expect that participants in both NoiBene conditions will show these outcomes. However, we hypothesized that the NB-G conditions will be more effective than the NB-WB in improving assertiveness. Besides treatment efficacy, we expect that students can benefit from the NB-G or NB-WB differently based on their specific behavioral and motivational patterns. Outcomes will be assessed at pre-, post-intervention and 6-months follow-up. In conclusion, we believe that NoiBene is a promising tool that can improve students' well-being, and it could have positive implications for preventing mental health disorders among students.